CEP control of dynamical Bloch oscillations in a bulk semiconductor via ultra-intense multi-THz fields - Meier, Torsten; Langer, F.; Schubert, O.; Hohenleutner, M.; Urbanek, B.; Lange, C.; Huttner, U.; Golde, D.; Kira, M.; Koch, S.W.; Huber, R. (CLEO: QELS_Fundamental Science)
Dynamical Bloch oscillations and coherent interband polarization in bulk GaSe are controlled by CEP-stable, ultra-intense multi-THz waveforms and result in the emission of phase-stable high-order harmonics covering 12.7 optical octaves from THz to VIS regimes.

Three-dimensional hybrid vortex solitons - Driben, Rodislav; Kartashov, Yaroslav V.; Malomed, Boris A.; Meier, Torsten; Torner, Lluis (New Journal of Physics)
We show, by means of numerical and analytical methods, that media with a repulsive nonlinearity which grows from the center to the periphery support a remarkable variety of previously unknown complex stationary and dynamical three-dimensional (3D) solitary-wave states. Peanut-shaped modulation profiles give rise to vertically symmetric and antisymmetric vortex states, and novel stationary hybrid states, built of top and bottom vortices with opposite topological charges, as well as robust dynamical hybrids, which feature stable precession of a vortex on top of a zero-vorticity soliton. The analysis reveals stability regions for symmetric, antisymmetric, and hybrid states. In addition, bead-shaped modulation profiles give rise to the first example of exact analytical solutions for stable 3D vortex solitons. The predicted states may be realized in media with a controllable cubic nonlinearity, such as Bose–Einstein condensates.

Soliton gyroscopes in media with spatially growing repulsive nonlinearity - Meier, Torsten; Driben, R.; Kartashov, Y. V.; Malomed, B. A.; Torner, L. (Physical review letters)
We find that the recently introduced model of self-trapping supported by a spatially growing strength of a repulsive nonlinearity gives rise to robust vortex-soliton tori, i.e., three-dimensional vortex solitons, with topological charges S≥1. The family with S=1 is completely stable, while the one with S=2 has alternating regions of stability and instability. The families are nearly exactly reproduced in an analytical form by the Thomas-Fermi approximation. Unstable states with S=2 and 3 split into persistently rotating pairs or triangles of unitary vortices. Application of a moderate torque to the vortex torus initiates a persistent precession mode, with the torus’ axle moving along a conical surface. A strong torque heavily deforms the vortex solitons, but, nonetheless, they restore themselves with the axle oriented according to the vectorial addition of angular momenta.

Digital Workers of the World Unite! A Framework for Critically Theorising and Analysing Digital Labour. In Special Issue: Philosophers of the World Unite! Theorising Digital Labour and Virtual Work - Definitions, Dimensions and Forms, eds. Marisol Sandoval, Christian Fuchs, Jernej A. Prodnik, Sebastian Sevignani and Thomas Allmer - Fuchs, Christian; Sandoval, Marisol (tripleC: Communication, Capitalism & Critique)

Introduction: Philosophers of the World Unite! Theorising Digital Labour and Virtual Work — Definitions, Dimensions, and Forms - Fuchs, Christian; Sandoval, Marisol; Prodnik, Jernej A.; Sevignani, Sebastian; Allmer, Thomas (tripleC: Communication, Capitalism & Critique)

Karl Marx y el estudio de los medios y la cultura hoy (Spanish translation by Roy Alfaro Vargas) - Fuchs, Christian (TELOS. Revista de Estudios Interdisciplinarios en Ciencias Sociales)

Karl Marx and the Study of Media and Culture Today - Fuchs, Christian (Culture Unbound)

WikiLeaks and the Critique of the Political Economy - Fuchs, Christian (WikiLeaks. From Popular Culture to Political Economy)

Digital Prosumption Labour on Social Media in the Context of the Capitalist Regime of Time - Fuchs, Christian (Time & Society)

Wikipedia. An Info-Communist Manifesto - Fuchs, Christian; Firer-Blaess, Sylvain (Television & New Media)